A computer experiment to simulate the dynamic behaviour of electric vehicles driven by switched reluctance motors. Issue 4 (October 2014) - Riba, Jordi-Roger; Garcia, Antoni; Romeral, Luís
The study of the dynamic behaviour of electric vehicles is being incorporated in the syllabuses of an increasing number of graduate and undergraduate courses. This paper analyses the basic mechanical and electric concepts of electric traction applied to automobiles. For this purpose, in this work the switched reluctance motor is analysed. A model based on MATLAB/Simulink to simulate the behaviour of both the electric motor and the vehicle dynamics is described. It allows students to gain a better understanding of the fundamental mechanical and electrical concepts by simulating the system behavior in an interactive and flexible manner.